Heat-stable Escherichia coli enterotoxin production in vivo. - Whipp, S C (1975)
Hysterectomy-derived, colostrum-deprived piglets were infected with enterotoxigenic Escherichia coli on day 4 of life. Samples of feces and intestinal contents were collected and tested in infant mice for enterotoxic activity. Positive enterotoxic responses were observed in mice given filtrates of feces and intestinal contents from piglets infected withe enterotoxigenic E. coli known to produce heat-stable enterotoxin but not heat-liabile enterotoxin in vitro. It is concluded that heat-stable enterotoxigenic E. coli induce diarrhea by production of heat-stable enterotoxin in vivo.